Surono Seniman Serba Bisa - Sriyadi Sriyadi (Institut Seni Indonesia Surakarta, 2009)
The process of an artistâ€™s journey through life is closely related to his or her social and cultural environment. Surono is an artist who is highly regarded, especially in the traditional art of wayang orang (a form of traditional Javanese stage show). He is not only skilled in the art of wayang orang but also as a dancer, singer, director, comedian, and Javanese gamelan musician, and is therefore often referred to as a â€œcompleteâ€ artist.Â Keywords: Artist, all-rounder, and creativity.